The Brief Experiential Avoidance Questionnaire: A Viable Alternative to aaq-ii? - Valencia, Pablo D. (Pensando Psicología, 2018)
Introduction: Experiential avoidance ( ea ) is a central concept in the study of psychopathology from a contextual-behavioral perspective. The Acceptance and Action Questionnaire ii ( aaq - ii ) has become the most commonly used measure of ea . However, some authors have seriously questioned its validity. In this context, the Brief Experiential Avoidance Questionnaire ( beaq ) is a promising alternative. Aim: The present study intended to translate the beaq into Spanish and analyze its psychometric prop- erties in a Peruvian sample. Materials and methods: The beaq was back-translated and a group of experts assessed the quality of the items. The questionnaire was responded by 376 Peruvian university students. The beaq - ii items were then subjected to an exploratory factorial analysis. Reliability estimators (H, α, ωT, ωTR) were also calculated. Results: The results did not support the supposed unidimensional nature of the beaq . Moreover, they suggested the presence of two factors called Avoidance of Suffering and Disconnection and Deacti- vation. Only the Avoidance of Suffering factor showed good reliability and could be easily interpreted. Conclusion: Future research should develop a new measure of ea based on the items of the Avoidance of Suffering factor. It is suggested that researchers continue to use aaq - ii until better measures of ex- periential avoidance are available.